Scarlet [compact disc, unabridged] - Lawhead, Stephen R., 1950- (Lawhead, Stephen R., 1950- King Raven trilogy (Oasis Audio), 2007)
With the Normans threatening to overrun Wales, forester Will Scarlet is being sentenced to die for a crime he didn't commit unless he betrays King Raven and his followers, and Bran ap Brychan makes a secret voyage to France to uncover a plot against the king.